Paraneoplastic pemphigus associated with chronic lymphocytic leukemia: A case report. Issue 8 (February 2017) - Jiang, Qu; Zhang, Bin Hong
Abstract: Rationale: Paraneoplastic pemphigus (PNP) is an autoimmune syndrome associated with neoplasms. The treatment approach principally includes suppressing the immunity, but its therapeutic effect is not satisfying. Patient concerns: We report a case of paraneoplastic pemphigus linked to chronic lymphocytic leukemia in a 63-year-old man. Diagnoses: At first, the patient was diagnosed with pityriasis rose caused by a viral infection. Biopsies for histology and immunofluorescence showed PNP, was treated with immunosuppressive and antiinfective therapy. Interventions: Immunosuppressive and antiinfective therapy were performed. Outcomes: The skin lesions of PNP were alleviated. However, the infections were aggravated and the disease progressed. The patient died of respiratory failure. Lessons: Treatment for PNP should be adapted to disease severity as early as possible. Antiinfection treatment should be timely and effective because infections are the most common complication that can lead to death.